2020
DOI: 10.3354/meps13506
|View full text |Cite
|
Sign up to set email alerts
|

The need to employ reliable and reproducible species identifications in coralline algal research

Abstract: Coralline algae perform important ecological roles in nearshore marine ecosystems globally by promoting the settlement of invertebrate larvae and enhancing biodiversity by creating habitat. However, these roles are severely threatened by global environmental changes. Most coralline algae are extremely difficult to identify, and DNA sequencing has revealed rampant inaccuracy of morpho-anatomical approaches to distinguish species, and even genera. If appropriate identification methods are not reported, or even u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Scientific effort in monitoring the abundance or ecology of coralline algae beyond simply acknowledging their collective presence or absence is lacking. This is hindered by the only recent understanding that coralline algae diversity is greater than previously believed (Gabrielson et al, 2018; Peña, Bélanger, et al, 2021; Twist et al, 2019) and extends far beyond the previous mostly morphological groupings and has important implications for much of the previous work in this field (Twist et al, 2020). Recent molecular work shows that some lineages of coralline algae are more vulnerable to OA than others, and that the projected adverse effects on coralline algal biodiversity have been greatly underestimated (Peña, Harvey, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific effort in monitoring the abundance or ecology of coralline algae beyond simply acknowledging their collective presence or absence is lacking. This is hindered by the only recent understanding that coralline algae diversity is greater than previously believed (Gabrielson et al, 2018; Peña, Bélanger, et al, 2021; Twist et al, 2019) and extends far beyond the previous mostly morphological groupings and has important implications for much of the previous work in this field (Twist et al, 2020). Recent molecular work shows that some lineages of coralline algae are more vulnerable to OA than others, and that the projected adverse effects on coralline algal biodiversity have been greatly underestimated (Peña, Harvey, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still many fundamental questions left unanswered in understanding the responses of coralline algae to OA that could offer insights regarding tolerant species or populations. Taxonomic variation in responses and its influence on other factors that we explored here can only be guessed at currently with the existing issues of nonmolecular identification in the majority of studies included here (Twist et al, 2020). Better integration of molecular work while assessing their response to OA is needed in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first molecular systematic study of the effects of ocean acidification on coralline algae and shows that this approach is essential for an accurate understanding of how the diversity of coralline algae is affected by CO 2 emissions (Twist et al, 2020). Highly diverse coralline algal assemblages were simplified under elevated levels of CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies identified 23 CCA species in Taiwan based on morphoanatomical evidence alone (Lewis & Norris, 1987; Wang, 1996). Without DNA barcoding, cryptic species diversity of CCA always goes undetected (reviewed in Twist et al, 2020). Recently, DNA barcoding studies revealed 13 CCA species in northern Taiwan, mostly in the TAR (Caragnano et al, 2018; Liu et al, 2018), bringing the total number of CCA species in Taiwan to 36.…”
Section: Discussionmentioning
confidence: 99%